Application of energy sustainable utilization strategy for highly efficient electro-Fenton treatment of antibiotics. Issue 1 (February 2022) - Xing, Luyi; Wei, Jia; Liu, Xiaohui; Zhang, Yifei; Xu, Mengdie; Li, Jiamei; Pan, Guoping; Li, Jun
Abstract: An innovative nitrogen-doped sludge-derived biochar (NSBC) electro-Fenton cathode was fabricated by a hydrothermal and pyrolysis combination method, which was applied to the degradation of sulfamethoxazole (SMX). The superficial characteristics of the optimal cathode (NSBC*@Ni-F) showed a large number of oxygen reduction reaction (ORR) electrocatalytic active sites under acidic conditions with high electrons transfer efficiency. The two nitrogen species (pyridinic-N and graphite-N) dominated the ORR electrocatalytic active sites. The H2 O2 yield (195.99 mg L −1 ) and corresponding current efficiency (73.69 ± 1.2%) using NSBC*@Ni-F cathode were 7 times higher than that of bare sludge biochar as cathode in EF system. An excellent SMX removal efficiency (95.72%) was achieved as well. The TOC removal achieved 85.11% and corresponding energy consumption reached as low as 12.03 kW h kg −1 . Rational reaction intermediates were put forward during EF procedure to predict and explore the SMX degradation pathway for water remediation. This study is hopeful to hew out a new road to develop eco-friendliness and cost-effective cathode material in EF system with adequate activity and reuse stabilization. Graphical Abstract: ga1 Highlights: Sludge biochar contributed to high electron transfer efficiency in electro-Fenton. Oxygen reduction reaction active sites was governed by pyridinic N and graphite N. The optimal NSBC*@Ni-F cathode generated 195.99 mg·L −1 H2 O2 in 50 min 95.7% sulfamethoxazole was degraded with NSBC*@Ni-F cathode. After 6th cycle of NSBC*@Ni-F, the SMX degradation rate was still above 91.32%.